2019
DOI: 10.1097/bor.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

New insights into IgG4-related disease: emerging new CD4+ T-cell subsets

Abstract: Purpose of review New insights into IgG4-related disease (IgG4-RD) have recently been obtained. A better understanding of the mechanisms underlying this disease is important for identification of therapeutic targets, which will lead to the development of specific strategies for treatment. Recent findings Infiltration of activated T follicular helper (Tfh) cells is observed in affected tissues of IgG4-RD. Such Tfh cells have a greater capacity than tonsillar Tfh cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 50 publications
1
23
0
1
Order By: Relevance
“…IL‐4 + Tfh cells were associated with AID + B cells predominantly outside germinal centers, and their frequency in blood correlated with serum IgG4 levels ( 68 ). Consistent with other rheumatic diseases, Tregs are found in IgG4‐RD lesions as well ( 71 , 72 , 73 , 74 ).…”
Section: High‐dimensional Views Of T‐cell Infiltrates In Rheumatic Diseasessupporting
confidence: 83%
“…IL‐4 + Tfh cells were associated with AID + B cells predominantly outside germinal centers, and their frequency in blood correlated with serum IgG4 levels ( 68 ). Consistent with other rheumatic diseases, Tregs are found in IgG4‐RD lesions as well ( 71 , 72 , 73 , 74 ).…”
Section: High‐dimensional Views Of T‐cell Infiltrates In Rheumatic Diseasessupporting
confidence: 83%
“…Multiple lines of evidence indicate that IgG4-RD is an autoimmune condition; however, the exact pathogenesis remains incompletely understood. There is an emerging consensus that the IgG4 antibodies in IgG4-RD are not pathogenic, and that T cells, especially CD4+ cytotoxic and T-follicular helper cells, have a more important role [ 3 ]. Elevations in serum and tissue IgG4 concentrations are not specific to IgG4-RD; they are also found in several other disorders such as multicentric Castleman disease, eosinophilic granulomatosis with polyangiitis, sarcoidosis and allergic diseases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-RD occurs mostly in middle to elderly people with a male to female ratio of 3:1 to 4:1, especially in AIP [12,[18][19][20]. The immunopathogenesis of IgG4-RD has not been clearly elucidated but previously studies have suggested that B cell and CD4 + T cells such as cytotoxic T lymphocytes (CTLs) and follicular helper T cells (T FH ) may be involved [10,21]. CD4 CTLs have been associated with fibrotic process through pro-fibrotic cytokine secretion, such as interferons (IFNs), transforming growth factor-β (TGF-β), and various interleukins (ILs), or through inducing their targeting cell to undergo apoptosis [21][22][23].…”
Section: Correlation Of Non-full-fledged Igg4-rd Patients With Different Comorbiditiesmentioning
confidence: 99%
“…The immunopathogenesis of IgG4-RD has not been clearly elucidated but previously studies have suggested that B cell and CD4 + T cells such as cytotoxic T lymphocytes (CTLs) and follicular helper T cells (T FH ) may be involved [10,21]. CD4 CTLs have been associated with fibrotic process through pro-fibrotic cytokine secretion, such as interferons (IFNs), transforming growth factor-β (TGF-β), and various interleukins (ILs), or through inducing their targeting cell to undergo apoptosis [21][22][23]. Different from excreting profi- brotic cytokines by CD4 + CTLs, CD4 T FH secretes IL-4 and IL-10 to stimulate B cell differentiation into IgG4-producing plasma cells [24].…”
Section: Correlation Of Non-full-fledged Igg4-rd Patients With Different Comorbiditiesmentioning
confidence: 99%